2013
DOI: 10.1371/journal.pone.0064396
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs as Potential Marker for Pulmonary Hypertension

Abstract: MircoRNAs (miRNAs) are small non-coding RNAs that govern the gene expression and, play significant role in the pathogenesis of heart failure. The detection of miRNAs in circulation of pulmonary hypertensive (PH) human subjects remains elusive. In the current study, we determined the pattern of miRNAs of mild-to-severe human PH subjects and, compared them with the control subjects by miRNA array. Blood was obtained using fluoroscopic and waveform guided catheterization from the distal (pulmonary artery) port of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 41 publications
6
100
1
Order By: Relevance
“…For example, circulating levels of miR-150 (72), miR-26a (73), miR-23a (74), and miR-125a (75) have been reported as reduced in patients with PAH. Dysregulation of entire sets of circulating miRNAs in PAH has also been described (74,76). Other miRNAs with known causative actions in PAH, such as the miR-130/301 family (20) and miR-210 (14), have been found to be elevated in the pulmonary circulation of patients with PH.…”
Section: Development Of Novel Mirna-based Diagnostic Platforms In Ph:mentioning
confidence: 97%
“…For example, circulating levels of miR-150 (72), miR-26a (73), miR-23a (74), and miR-125a (75) have been reported as reduced in patients with PAH. Dysregulation of entire sets of circulating miRNAs in PAH has also been described (74,76). Other miRNAs with known causative actions in PAH, such as the miR-130/301 family (20) and miR-210 (14), have been found to be elevated in the pulmonary circulation of patients with PH.…”
Section: Development Of Novel Mirna-based Diagnostic Platforms In Ph:mentioning
confidence: 97%
“…It has been shown that a collection of miRNAs, such as miR-451 and miR-1246, decreased, while several miRNAs, such as miR-23b, miR-130a and miR-191, increased in the plasma of patients with PAH. These studies might have important implications for clinical research aiming to establish whether miRNAs could be used as biomarkers for PAH [57]. However, as the currently available methods used for PAH detection are limited to catheterization performed under X-ray fluoroscopy, extensive work on developing simple and effective detection methods using high specificity and sensitivity plasma markers is needed.…”
Section: Serum Mirnas Might Serve As Biomarkers For Vascular Diseasementioning
confidence: 99%
“…Many different pathways are involved in PAH, and multiple biomarkers for PAH have been described, including atrial natriuretic peptide and brain natriuretic peptide (BNP), 28 N-terminal pro-BNP, 29 cardiac troponin T, 30 uric acid, 31 urinary prostaglandin metabolites, 32 endothelial NO synthase (eNOS) and dimethylarginines, 33,34 ET-1 and ET-1:ET3 ratio, 35,36 circulating von Willebrand factor, 37,38 biomarkers of inflammation and oxidative stress such as cytokines (IL-1a, -2, -4, -6, -8, -10 and 12p70, TNF-b, MCP-1 and osteopontin), 39-42 C-reactive protein, 43 50 have also been identified as biomarkers in PAH, with possible implications on outcomes. It is of importance to differentiate markers that indeed reflect right ventricular dysfunction from markers of endothelial dysfunction and finally markers that might predict potential reversibility of the pulmonary vascular lesions; the latter being the one that will discriminate operable vs. inoperable patients.…”
Section: Myers Po Et Almentioning
confidence: 99%
“…53 Micro-RNAs are small, endogenously expressed non-coding RNAs that regulate gene expression at a post-transcriptional level. 50 Micro-RNAs have been implicated in many different settings of cardiovascular remodeling, including blood vessel development, angiogenesis and vascular injury. 54, 55 They have been identified as biomarkers for early diagnosis in acute myocardial infarction and heart failure.…”
Section: Myers Po Et Almentioning
confidence: 99%
See 1 more Smart Citation